Antibacterial action of copperions on food-contaminating bacteria - Zanzen, Ulrike (Acta Biologica Szegediensis, 2013)
Silver and copper ions are widely used as antibacterial agents but the basic molecular mechanism of this effect is still poorly understood. The analysis of our investigation gives clear indications that Ag+ do react with the bacterial cells and do not stay as silver in the system. Significant lower silver cysteine content coupled with higher silver histidine content in Gram-positive cells indicate that the peptidoglycan multi-layer could be buffering the biocidal effect of silver for the Gram-positives at least in part. Interaction with DNA or proteins can occur through Ag-N bonding. The formation of silver cysteine can be confirmed for both bacterial cell types which thus supports the hypothesis that enzyme catalyzed reactions and the electron transport chain within the cell is disrupted. The antibacterial property of copper is attributed mainly to adhesion with bacteria because of their opposite electrical charges, resulting in a reduction reaction at the bacterial cell wall. Nanoparticles with a larger surface-to-volume ratio might provide more efficient means for antibacterial activity. First results suggest that copper ions do not react compared to silver ions.